The impacts of knowledge interaction with manufacturing clients on KIBS firms innovation behaviour - Poh-Kam Wong; Zi-Lin He (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Knowledge-intensive business services (KIBS) have been posited to play a critical role as innovation agent and knowledge broker in the new economy. While a substantial part of the literature on KIBS stresses their function as an innovation agent to their clients' innovation process and their contributions to knowledge transfer and diffusion in innovation systems, little attention has been paid to the internal innovation dynamics of KIBS firms. However, the interactive service relationship between KIBS firms and their clients is essentially a bilateral learning process that is supposed to also expand the innovation capabilities of KIBS firms. Based on a sample of 181 KIBS firms in Singapore, we investigate the specific impacts of client linkages on KIBS firms' innovation behaviour. We find that KIBS firms that engage in providing innovation support to manufacturing clients exhibit higher level of innovation behaviour. However, client size is not a significant determinant of KIBS innovation. These results are further confirmed by the importance of social capitals and spatial proximity for KIBS firms' successful innovation support provision to manufacturing clients.
Keywords: O30; O31; O32; 330; knowledge-intensive business services (KIBS); knowledge interaction; innovations systems; Unternehmensdienstleistung; Wissen; Wissenstransfer; Innovationsmanagement